Economic growth and public debt: patterns and lessons between advanced, emerging, and declining growth economies - Shamu, Mbali N.D. (University of the Witswatersrand, Johannesburg, 2023)
This research investigates the causal relationship between economic growth and public debt for economies in different growth categories: advanced, emerging and declining-growth economies, the latter being a new category introduced by this study. The study aims to answer the question: Does the level of economic growth affect public debt accumulation? The results reveal that in advanced economies growth is not a significant explanatory variable for public debt accumulation nor is there a significant long-run relationship between growth and public debt. For emerging and declining growth economies, the opposite holds- economic growth is a significant explanatory variable for public debt accumulation
A Master’s Thesis submitted in fulfilment of the Degree of Master of Commerce (Economics) in the School of Economics and Finance, University of the Witwatersrand
Keywords: UCTD; Economic growth; Public debt; Emerging and declining-growth economies; Public debt; SDG-8: Decent work and economic growth